Whole transcriptome sequencing and ceRNA regulation network profiling of heat acclimation in protecting against heat stress injury in rat myocardium - LiJun Fan; JiaJun Chen; QingHan Zhang; MingXiao Song; ZiYi Guo; Xuewei Chen; Junyu Lu; Jing Wang (PLoS ONE, 2026)
Heat acclimation (HA) has emerged as a proven protective intervention to augment thermotolerance and mitigate heat stress (HS)-induced myocardial injury. Despite its clinical significance, the regulatory roles of noncoding RNAs associated with HA-mediated cardioprotection remain largely unexplored. This study conducted comprehensive transcriptomic profiling to delineate the molecular mechanisms underlying HA-induced cardioprotection against HS. Using well-characterized rat models of HS and HA preconditioning, we performed high-throughput sequencing on myocardial tissues to map circRNA/lncRNA expression landscapes. Bioinformatic analyses were integrated with functional validation to identify key regulatory elements. HA preconditioning markedly attenuated HS-induced injury, reducing inflammatory cytokines (IL-1β ↓ 24.36%, IL-4 ↓ 11.3%) while elevating IL-6 (+25.67%), suggesting immunomodulatory rewiring. HS leads to elevated serum HSP70 levels. Analysis identified nine core molecular candidates—miR-196c-5p, miR-212-3p, miR-212-5p, Rffl, Rassf1, Ppp3cc, Zbtb20, Cdh5, and Cxcl2 —and delineated two central ceRNA regulatory axes: MSTRG.6276.3–miR-196c-5p– Rffl and MSTRG.4016.1–miR-122-5p– Rassf 1. These networks potentially coordinate mitochondrial integrity, hypoxic adaptation, and apoptotic regulation through modulation of inflammatory signaling, metabolic homeostasis, and calcium pathways. The findings establish a noncoding RNA-defined regulatory framework for HA-mediated cardioprotection, revealing novel therapeutic targets for cardiovascular disorders triggered by thermal stress.